Exploring preferences for improved fish species among farmers: A discrete choice experiment applied in rural Odisha, India - Manyise, Timothy; Dam Lam, Rodolfo; Lozano, Denise; Panemangalore, Arun; Shenoy, Neetha; Chadag, Vishnumurthy Mohan; Benzie, John; Rossignoli, Cristiano (Elsevier, 2024)
The diversification of farmed fish species to include improved farmed fish species promise to generate greater gains for rural households and help to address challenges of food and nutrition security in rural India. Adoption of genetically improved farmed fish species, however, depends on the farmers' willingness to pay (WTP) for the related attributes relative to local farmed fish species. We explored fish species preferences among small aquaculture farmers distributed across the central, northern, and southern districts of Odisha, India. Odisha presents an interesting case to understand farmers fish preference given the Indian government's recent policy focus towards fish species diversification to address complex challenges of rural poverty and food & nutrition insecurity. The results showed that farmers are willing to adopt fish species with higher survival rate, and higher growth rate. However, farmers are yet to appreciate exotic species such as GIFT relative to indigenous (Indian Major Carps). This study suggests that policy decisions aimed at enhancing the diversification of farmed fish species should encompass not only providing input subsidies to enable farmers to experiment with improved fish seeds but also dedicating efforts to bolster diversified fingerling supply. This includes both common farmed species and new species, coupled with initiatives to raise awareness of the tangible benefits derived from improved species and promote their market acceptance.